Left ventricular systolic dysfunction in outpatients with peripheral atherosclerotic vascular disease: prevalence and association with location of arterial disease. (26th April 2014) - Hedberg, Pär; Hammar, Charlotta; Selmeryd, Jonas; Viklund, Josefin; Leppert, Jerzy; Hellberg, Anders; Henriksen, Egil
<x xml:space="preserve">Abstract</x> Aims We aimed to determine the prevalence of left ventricular systolic dysfunction (LVSD) in outpatients with peripheral atherosclerotic vascular disease (PAVD). Further, the associations of stenotic internal carotid artery disease (SICAD) and lower extremity artery disease (LEAD) with LVSD were evaluated. Methods and results In the Peripheral Artery Disease in Västmanland study, consecutive outpatients with ultrasonographically identified mild to severe stenosis in the internal carotid artery or symptoms of claudication combined with either ankle brachial index of ≤0.90 or ultrasonographic occlusive findings were included (n = 437). Population‐based control subjects were matched to the patients (n = 395). LVSD was defined as echocardiographically determined left ventricular ejection fraction (LVEF) <55%, and moderate or greater LVSD was defined as LVEF <45%. The prevalence of LVSD was significantly greater in patients than in controls (13.7% vs. 6.1%, P < 0.001). The prevalence of moderate or greater LVSD in participants not on treatment with a combination of angiotensin‐converting enzyme inhibitor and beta‐blocker was 2.3% in patients and 1.3% in controls (P = 0.31). When LEAD and SICAD were analysed together, adjusted for potential confounders, SICAD [odds ratio (OR) 2.54, 95% confidence interval (CI) 1.03–6.32], but not LEAD (OR 1.59, 95% CI 0.80–3.18), was independently associated with LVSD. Conclusions In outpatients with PAVD, we found a 13.7% prevalence of LVSD. However, the prevalence of at least moderate LVSD in patients not on treatment with angiotensin‐converting enzyme inhibitor and a beta‐blocker was only 2.3% and not significantly different from controls. Stenotic artery disease in the internal carotid artery, but not in the lower extremities, was independently associated with LVSD.